(untitled) (Physical Education, Health and Social Sciences, 2025)
This study is conducted for representation of critical discourse analysis of the protestor’s language expresses through banners/ placards to record the protest against dilemma faced from heavy rain of 2020 in Karachi. The primary goal of the study is Critical Discourse Analysis of banners/ placard’s language used in protest demonstration of rain mob to attract the attention of main frame media and government authorities. Qualitative research was carried out by complying the Fairclough’s three-dimensional approach on the selected placards. The protesters launched their campaign for the remedy of their grievances/ hardships in different part of the Karachi. The data of the research was collected from the internet resources. The banner’s language and slogans portrayed are opted for critical discourse analysis to ascertain the gravity of the issue. The critical discourse analysis of the banners/ placards data depicts the difficulties faced due to poor infrastructure for the drainage of the rain water and lack of trustworthiness of protestors on provincial government and calling of Federal government for help.